Od abecadlnika do encyklopedii, czyli o picturebooku Iwony Chmielewskiej abc.de - Chwirot, Agata (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
Iwona Chmielewska’s picturebook abc.de published in 2015 has been called a ‘dictionary’, ‘primer’, ‘ABC book’ and it has been compared to an encyclopaedia. Early-concept or concept books have been mentioned in its context, as well as the title of other books by Chmielewska, ‘thinking ABC’, this time as a specific name for a particular type of work. The terms ‘rebus’, ‘puzzle’, ‘riddle’, ‘intellectual game’ also appear frequently. All this together suggests how complex and multi-layered the book is and how much it draws on various forms. The aim of this article, therefore, is to look at what forms, in what way and for what purpose Iwona Chmielewska uses in abc.de and how it all relates to contemporary trends in the development of non-fiction picturebooks.